PHYSICS AND SPORTS: THE SCIENCE BEHIND PERFORMANCE (Fiep Bulletin - online, 2025)
Introduction: Physics plays a fundamental role in analyzing and optimizing sports performance, offering tools and theories that help understand the movements, forces and energies involved in sports. From studying the biomechanics of movement to analyzing ideal conditions for performance, physics provides insights into how athletes can improve their skills and prevent injuries. The study of science applied to sports becomes increasingly relevant, given the growing interest in maximizing physical potential and reducing injury risks. Objectives: This study seeks to review how physical principles apply to sports, providing an understanding of the science that drives sports performance. The research aims to: Explore the fundamental principles of physics applied to movement and sports performance, analyze the main forces involved in different modalities, such as gravity, friction and air resistance and investigate how knowledge of these forces can be used to optimize athletes' performance and reduce injuries. Methods: This is a narrative review study, which analyzes and synthesizes the existing literature on the application of physics concepts in sports. The methodology includes the review of scientific articles, books, and relevant secondary sources, selected according to the quality and depth in the analysis of physical principles and their practical applications in various sports. Results: 12 articles were chosen, 1 from each topic listed. Conclusion: Physics plays a crucial role in optimizing sports performance, from analyzing movement to improving equipment and strategies. With technological advancement, the integration of Physics with other areas promises to further transform the sport.